Analysis of Mathematical Knowledge of Journalists in West Kalimantan Based on Journalistic Profile - Heriyanto Heriyanto; Bistari Bistari; Silvia Sayu; M. Rifat (Ridwan Institute, 2023)
This study aims to determine the basic mathematical knowledge of journalists in West Kalimantan. A total of 20 tests in the form of multiple-choice questions were given to 33 respondents to find out their basic knowledge of mathematics. All respondents worked as journalists in various media in West Kalimantan. The test results showed that 39.39 percent of respondents had low mathematical knowledge, 36.36 percent on medium criteria, 18.18 on high criteria, and 6.07 percent on very low criteria. The results of this test can be a baseline for improving the mathematical knowledge of journalists through various trainings or workshops. Mathematical knowledge is needed for journalists to increase credibility in news writing.